Experience of Community Neurologists Providing Care for Patients With Neurodegenerative Illness During the COVID-19 Pandemic. (7th September 2021) - Ayele, Roman; Macchi, Zachary A.; Dini, Megan; Bock, Meredith; Katz, Maya; Pantilat, Steven Z.; Jones, Jacqueline; Kluger, Benzi M.
Abstract : Objective: Health care delivery systems transformed rapidly at the beginning of the coronavirus disease 2019 (COVID-19) pandemic to slow the spread of the virus while identifying novel methods for providing care. In many ways, the pandemic affected both persons with neurologic illness and neurologists. This study describes the perspectives and experiences of community neurologists providing care for patients with neurodegenerative illnesses during the COVID-19 pandemic. Methods: We conducted a qualitative study with 20 community neurologists from a multisite comparative-effectiveness trial of outpatient palliative care from July 23, 2020, to November 11, 2020. Participants were interviewed individually about the impact of the coronavirus disease 2019 (COVID-19) pandemic on their professional and personal lives. Interviews were analyzed with matrix analysis to identify key themes. Results: Four main themes illustrated the impact of the pandemic on community neurologists: (1) challenges of the current political climate, (2) lack of support for new models of care, (3) being on the frontline of suffering, and (4) clinician self-care. Taken together, the themes capture the unusual environment in which community neurologists practice, the lack of clinician trust among some patients, patient and professional isolation, and opportunities to support quality care delivery. Conclusions: The COVID-19 pandemic and pandemic politics created an environment that made care provision challenging for community neurologists. Efforts to improve care delivery should proactively work to reduce clinician burnout while incorporating support for new models of care adopted due to the pandemic. Trial Registration Information: ClinicalTrials.gov identifier: NCT03076671.